The Relationship between Firefighters' Work Demand and Work-related Musculoskeletal Disorders: The Moderating Role of Task Characteristics - Justice K. Kodom-Wiredu (Elsevier, 2019)
Background: Emergency workers such as firefighters are cataloged within the most demanding and injurious professions globally. Considering the health and safety implications in firefighting, a lot of research needs to be conducted to examine how firefighters' task characteristics and their work demand influence the development of work-related musculoskeletal disorders (WMSDs). This study therefore examines how the task characteristics of firefighters moderates the relationship between their work demand and the development of WMSDs. Methods: Convenient sampling was employed to select 320 firefighters in the Greater Accra region of Ghana. Data were analyzed using descriptive statistics, correlation, and regression. Results: The findings revealed that work demand and task characteristics have significant positive effects on WMSDs. Again, the task characteristics of firefighters moderates the relationship between their work demand and WMSDs. Conclusion: Since the study shows that task characteristics influences the relationship between work demand and WMSDs, it is vital for managers to constantly modify the nature of tasks performed by and work demand of emergency workers to minimize the development of WMSDs and other industrial health complications. Keywords: firefighters, task characteristics, work demand, work-related musculoskeletal disorders